Ondřej Daniel: Bigbít nebo turbofolk. Představy migrantů z bývalé Jugoslávie [Big beat or Turbofolk. Imaginations of Migrants from the Former Yugoslavia]: AntropoEdice, sv. 3. Praha: AnthropoWeb 2013, 155 pp. - Slavková, Markéta (Lidé města, 2014)
A review of the book by Ondřej Daniel.